Facilitated Synthesis of Mg2Ni Based Composites with Attractive Hydrogen Sorption Properties - Eli Grigorova (Materials, 2021)
Composites based on Mg2Ni with 5% activated carbon from apricot stones (ACAP) have been prepared by ball milling and subsequent annealing in hydrogen atmosphere. The purpose of the primary metal (Mg, Ni, and V) milling was to reduce the particle size and achieve a good contact between them, without forming intermetallic compounds. During hydriding/dehydriding at 300 °C the amount of the Mg2Ni phase progressively increased, and after 10 cycles about 50% Mg2(Ni,V) was achieved. The hydrogenation produced mainly Mg2NiH4, but small amounts of MgH2 and VHx were also detected in the powder mixture. Relatively high hydrogen storage capacity and fast hydriding/dehydriding kinetics of the Mg2.1Ni0.7V0.3—5 wt.% ACAP composite were determined both from hydrogen gas phase and electrochemically.